PENGATURAN LAMPU LALU LINTAS BERBASIS MIKROKONTROLER ATMEGA8535 - Alamsyah, Alamsyah (MEKTEK, 2012)
It has built a simulator traffic lights to set the length of time the light is green, yellow, and red on a two-way street. Setting the length of time the lighting is made on the C language program listings using the software (software) proteus to solve traffic management problems. In traffic control simulator output variable is the length of time the green light for two lanes. The output obtained from the listing program using C language software to be used as reference data in the creation of programs to determine the duration of the green light. The program then implanted into the ATmega8535 microcontroller IC.The results of the simulator design a traffic light shows, the C language can be used as decision-makers to determine the length of time the green light depending on the microcontroller as a control.